(untitled) (Research, Society and Development, 2024)
Scenario Planning in Education essentially seeks a new way of thinking about education. The future scenario is a technique, a methodology that serves to outline possible ways to predict it. We can draw random conjectures, trying to conceive, build horizons, in order to evaluate different possibilities, thus outlining a way of knowing what this future may or may not hold for us. When strategically planning a scenario, one must incorporate the visions, concepts, and techniques that will be taken into consideration to predict it, as the great difference of any institution is anticipating moments of crisis. In this sense, the methodology used has a bibliographical character based on theorists such as Bryson, Marcial, Minayo, among others who bring essential information to their studies for better writing of the article. This article sought to highlight the importance of Scenario Planning, placing it as a mechanism of great value for managers and employees in decision-making. Concepts on the subject and future scenarios were listed from the perspective of several authors, which can contribute significantly to the reflection of everyone who is part of the organization/institution and who is involved not only directly, but also indirectly, since both Strategic planning regarding the construction of future scenarios affects everyone involved. The article aims to present the notable fact that the construction of scenario planning within the educational environment is of fundamental importance to prepare in advance, aiming to foresee future events that may or may not occur.